2016
DOI: 10.1016/j.envpol.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Did policies to abate atmospheric emissions from traffic have a positive effect in London?

Abstract: A large number of policy initiatives are being taken at the European level, across the United Kingdom and in London to improve air quality and reduce population exposure to harmful pollutants from traffic emissions. Trends in roadside increments of nitrogen oxides (NO), nitrogen dioxide (NO), particulate matter (PM), black carbon (CBLK) and carbon dioxide (CO) were examined at 65 London monitoring sites for two periods of time: 2005-2009 and 2010-2014. Between 2005 and 2009 there was an overall increase in NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 30 publications
2
59
0
1
Order By: Relevance
“…brake wear) are considered to be significant sources of PM, which is then re-suspended by trafficrelated turbulence 25,26 . In an examination of air pollutant trends in London between 2005-2009 and 2010-2014, Font and Fuller 27 found that abatement measures in some locations were offset by changes in traffic flow; that is, that increased non-exhaust sources of coarse PM, including road wear by heavier vehicles, offset reductions in exhaust emissions. This has implications for the assumed benefit of a move towards the use of electric vehicles for ambient air quality 28 .…”
Section: Introductionmentioning
confidence: 99%
“…brake wear) are considered to be significant sources of PM, which is then re-suspended by trafficrelated turbulence 25,26 . In an examination of air pollutant trends in London between 2005-2009 and 2010-2014, Font and Fuller 27 found that abatement measures in some locations were offset by changes in traffic flow; that is, that increased non-exhaust sources of coarse PM, including road wear by heavier vehicles, offset reductions in exhaust emissions. This has implications for the assumed benefit of a move towards the use of electric vehicles for ambient air quality 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, understanding the association of allergic diseases with a specific source of air pollution is important because this enables the relevant authorities to establish a clear target of intervention for reducing air pollution and preventing subsequent adverse health effects. Specifically, exposure to traffic-related air pollution (TRAP) has become of particular interest because traffic-related interventions, such as implementation of diesel retrofit programs, restriction of high emission vehicles, and accommodation of energy-efficient vehicles, are highly practical options for reducing air pollution in many countries [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large achievements in tail-pipe emission reductions due to the EUROx directives (AIRUSE, 2016), an important fraction of traffic emissions remain uncontrolled, namely non-exhaust emissions. Indeed, studies have demonstrated that the relative importance of non-exhaust emission is increasing, and is already becoming the dominant local source in cities Font and Fuller, 2016). Political and technological actions are therefore urgently needed, in order to regulate and minimize emissions from brakes, tires and road wear as well as from road dust resuspension.…”
Section: Introductionmentioning
confidence: 99%